Determinants of lifetime unemployment: a micro data analysis with censored quantile regressions - Achim Schmillen; Joachim Möller (Institute for the Study of Labor (IZA), 2010)
The empirical literature on unemployment almost exclusively focuses on the duration of distinct unemployment spells. In contrast, we use a large German administrative micro data set for the time span 1975-2004 to investigate individual lifetime unemployment (defined as the total length of all unemployment spells over a 25-year period). This new perspective enables us to answer questions regarding the long-term distribution and determinants of unemployment for West German birth cohorts 1950-1954. We find that lifetime unemployment is highly unevenly distributed and employ censored quantile regressions to show that, for men, pursuing a disadvantageous occupation early in the professional career leads to a significantly higher amount of lifetime unemployment.
Keywords: J64; J24; 330; Lifetime unemployment; censored quantile regressions; occupation-specific human capital; Arbeitslosigkeit; Lebenszyklus; Erwerbsverlauf; Qualifikation; Ungelernte Arbeitskräfte; Schätzung; Deutschland